Estimation of Kidney Function and Haematological Parameters of Methanol Leaf Extract of Annona senegalensis on Diethyl Nitrosamine-Induced Hepatocellular Carcinoma in Rats - Umaru, Isaac John; Absalom, Augustine; Udoh, Mary Athanasius; Omolara, Mosugu Ovayoza; Okang, Ogar Fonne; Akem, Ingwu Joseph; Tansaba, Akafa Andes; Frank, Otashu Kenneth; Philip, Shadrach (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Hepatocellular carcinoma (HCC) is a major cause of liver-related mortality worldwide, often linked to oxidative stress and hepatotoxicity induced by carcinogens such as diethylnitrosamine (DEN). This study investigates the biochemical and hematological effects of methanol leaf extract of Annona senegalensis on DEN-induced HCC in male albino rats. Thirty rats were divided into six groups: normal control, negative control (DEN-induced), positive control (DEN + silymarin), and three treatment groups receiving A. senegalensis extract at 200 mg/kg, 400 mg/kg, and a combined regimen. DEN exposure significantly elevated serum biomarkers of liver damage, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and bilirubin. Treatment with A. senegalensis extract at 400 mg/kg markedly reduced ALT, AST, and ALP levels compared to the negative control, demonstrating hepatoprotective potential. Hematological analysis revealed a decline in white blood cell (WBC) count across treatment groups, suggesting possible immunosuppressive effects. Red blood cell (RBC) count and hemoglobin (HGB) levels decreased at 200 mg/kg but increased at 400 mg/kg, indicating a dose-dependent erythropoietic effect. Platelet (PLT) counts, elevated in the DEN-induced group, were normalized by the extract. These results suggest that A. senegalensis contains bioactive compounds with hepatoprotective and hematomodulatory activities. While higher doses improved liver function and hematological balance, the observed immunosuppressive tendencies highlight the need for further mechanistic studies. The findings support the therapeutic potential of A. senegalensis in hepatocellular carcinoma management, warranting future preclinical and clinical evaluation.